Functional rescue of dystrophin-deficient mdx mice by a chimeric peptide-PMO - Yin, H; Moulton, H; Betts, C; Merritt, T; Seow, Y; Ashraf, S; Wang, Q; Boutilier, J; Wood, MJA (Cell Press, 2010)
Splice modulation using antisense oligonucleotides (AOs) has been shown to yield targeted exon exclusion to restore the open reading frame and generate truncated but partially functional dystrophin protein. This has been successfully demonstrated in dystrophin-deficient mdx mice and in Duchenne muscular dystrophy (DMD) patients. However, DMD is a systemic disease; successful therapeutic exploitation of this approach will therefore depend on effective systemic delivery of AOs to all affected tissues. We have previously shown the potential of a muscle-specific/arginine-rich chimeric peptide-phosphorodiamidate morpholino (PMO) conjugate, but its long-term activity, optimized dosing regimen, capacity for functional correction and safety profile remain to be established. Here, we report the results of this chimeric peptide-PMO conjugate in the mdx mouse using low doses (3 and 6 mg/kg) administered via a 6 biweekly systemic intravenous injection protocol. We show 100% dystrophin-positive fibers and near complete correction of the dystrophin transcript defect in all peripheral muscle groups, with restoration of 50% dystrophin protein over 12 weeks, leading to correction of the DMD pathological phenotype and restoration of muscle function in the absence of detectable toxicity or immune response. Chimeric muscle-specific/cell-penetrating peptides therefore represent highly promising agents for systemic delivery of splice-correcting PMO oligomers for DMD therapy.